Análise e avaliação do projeto de educação ambiental “Vida à Água” voltado à gestão de bacias hidrográficas (Pinhais-PR) - Sá, Patricia Zeni de (2013)
This research aims to analyze qualitatively and quantitatively the proposed Environmental Education project "Vida à Água" in order to evaluate its teaching-learning as an extension project, aimed at the conservation of water resources. Fieldwork was developed in Municipal Schools: Felipe Zeni, Aroldo de Freitas and Marins de Souza Santos in a period of seven months (March-October 2012) with all the teachers and students of 4th and 5th years of primary school. These schools were used two research methods, the first using mind maps, which were conducted with students before and after the play activity developed by the Water Life Project and the second method was the application of questionnaires, which were answered by students in classrooms and teachers through semi-structured interviews. The project evaluation was performed with two different groups, one group of teachers and students who participated in the project Life Water and others not involved in the project. The two groups have basically the same characteristics. The mind maps were applied to 133 students in the group of project participants. After analyzing and interpreting the data it was observed that the percentage of positive responses after participation in leisure activity had a significant increase, especially in relation to the origin of river water / raw water (25%), sewer (24%) and treatment drains (24%). Regarding the questionnaires were administered 473, 420 for these students, with 223 students participating correspond Project Life Water will not and 197 students participating in the project. For teachers were applied 53 questionnaires from interviews with 25 of these teachers participated in the project Life Water and 28 did not participate. Analyzing the data and using the chi-square statistical method, it was identified that the group of participants of Project Life Water made a most significant result compared to the group of non-participants in relation to the transmission of knowledge, environmental perceptions and sensitization of teachers and students about conservation of water resources, making them feel more motivated for learning of environmental issues.